"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Histoire de la sexualité. 1: La volonté de savoir - Foucault, Michel (Collection tel, 2014)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; har4600; histoire et politique; incontournable; philosophie; postmodernisme; premier cycle; périodes historiques; sciences humaines; sexualité; soc2014; thématiques

Du féminisme (de la troisième vague) et du postmoderne - Oprea, Denisa-Adriana (Recherches féministes, 2008)
Le présent article se veut une contribution d'ordre théorique. En premier lieu, il procède à une présentation du féminisme de la troisième vague, établit ses rapports avec le féminisme de la deuxième vague et met en valeur sa portée heuristique. En deuxième lieu, il propose une délimitation rigoureuse du champ postmoderne. Deux attitudes sont ainsi décelées, soit ici le postmoderne du vide et le postmoderne du décentrage. En troisième lieu, ce travail pense ensemble, dans leurs effets de sens communs et dans leurs différences, le postmoderne et le(s) féminisme(s), tout particulièrement le féminisme de la troisième vague.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; europe; fem1000; histoire et politique; mouvements féministes; occident; philosophie; postmodernisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

De la construction du genre à la construction du « sexe » : les thèses féministes postmodernes dans l’oeuvre de Judith Butler - Baril, Audrey (Recherches féministes, 2007)
La philosophe Judith Butler est aujourd’hui reconnue comme une figure marquante du féminisme postmoderne. L’originalité de sa pensée a fortement influencé le champ des études féministes, gaies et lesbiennes et queers. Dans ses théorisations, Butler procède à la déconstruction du naturalisme et du fondationnalisme sous-tendant les catégories de sexe et de genre. Cette prise de position constructiviste l’amène à réfléchir et à militer pour la reconnaissance sociale et politique des différents genres et des multiples sexualités. Bien que Butler soit devenue une référence incontournable à l’échelle internationale, ses travaux ont fait l’objet de peu d’analyses au Québec. Cet article veut favoriser une meilleure compréhension des postulats philosophiques et épistémologiques de son oeuvre. Pour ce faire, une analyse des concepts clés de la pensée de Butler, notamment celui de performativité du genre, est d’abord effectuée. Puis les principales critiques à l’égard de ses thèses sont examinées et, finalement, les réponses de Butler à ces critiques sont présentées.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; com5170; cours; discipline; fem1000; genre; har4600; identités LGBTQIA2+; philosophie; pol4212; postmodernisme; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sex1183; thématiques; épistémologie; états-unis; études culturelles

Feminist epistemology after postmodernism: Critiquing science, technology and globalisation - Braidotti, Rosi (Interdisciplinary Science Reviews, 2007)
This article provides a reasoned overview of contemporary developments within feminist theories of the subject after the decline of postmodernist thought. It stresses the foundational importance of feminist situated epistemology, and hence of a brand of materialism that stresses embodiment and embedded perspectives. The article explores neo-materialist feminist theories in a number of areas, with special emphasis on science and technology studies and critiques of globalisation. It argues that the neo-materialist trend results in a new call for an ethics attuned to the complexity of our era.
Keywords: approches et analyses; bio-technologie; discipline; environnement; féminisme matérialiste; philosophie; postmodernisme; projet charge mentale; ressource en ligne; sciences humaines; thématiques; épistémologie

Sujets de sexe/genre/désir - Butler, Judith (Trouble dans le genre : pour un féminisme de la subversion, 2005)
Keywords: amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; philosophie; postmodernisme; premier cycle; queer; régions géographiques; sciences humaines; sexe; sexualité; thématiques; états-unis

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Thinking gender, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

Feminists theorize the political - Butler, Judith; Scott, Joan Wallach (Routledge, 1992)
On a dit que l'utilisation de la « théorie » dans l'analyse féministe menaçait le féminisme en tant que force politique. Cette collection de travaux d'éminentes universitaires féministes aborde la question du statut politique de la théorie du poststructuralisme au sein du féminisme. Contre l'idée que l'utilisation du post-structuralisme affaiblit nécessairement le féminisme, « Feminists Theorize the Political » affirme le débat contemporain sur la théorie comme politiquement riche et conséquent. En jetant les bases théoriques du volume, Butler et Scott ont posé un certain nombre de questions à d'éminents juristes, critiques littéraires, philosophes, théoriciens politiques, historiens et théoriciens de la culture. Les essais ne résolvent pas les questions mais génèrent des directions nouvelles et productives pour celles-ci. Le volume dans son ensemble valorise le pouvoir troublant et politique de la théorie. Les essais de "Feminists Theorize the Political" abordent les questions qui émergent de la convergence du féminisme et du poststructuralisme : qu'advient-il de la critique féministe lorsque les fondements traditionnels - l'expérience, l'histoire, les normes universelles - sont remis en question ? La théorie féministe peut-elle problématiser la notion de sujet sans perdre son effectivité politique ? Quelle version du sujet doit être interrogée, et comment ce questionnement ouvre-t-il des possibilités de reformulation de l'agence, du pouvoir et des sites de résistance politique ? Quelles sont les conséquences d'une reformulation spécifiquement féministe de la différence ? Quels sont les usages et les limites d'une critique poststructuraliste de la logique binaire pour la théorisation des différences raciales et de classe, la position du subalterne ? Cette anthologie représente une diversité de travaux théoriques au sein de la théorie féministe à forts enjeux politiques. Bien que tous les auteurs ne souscrivent pas au poststructuralisme (et peu concéderaient que le poststructuralisme est une entreprise monolithique), chacun propose une analyse féministe innovante qui est d'une certaine manière motivée dans et par le défi poststructuraliste. 'Feminists Theorize The Political' aborde une série de préoccupations féministes, y compris la liberté productive, la loi anti-discrimination, le viol et la formulation du pouvoir en termes d'exclusion, de différence et de hiérarchie. chacune propose une analyse féministe innovante qui est en quelque sorte motivée dans et par le défi poststructuraliste. 'Feminists Theorize The Political' aborde une série de préoccupations féministes, y compris la liberté productive, la loi anti-discrimination, le viol et la formulation du pouvoir en termes d'exclusion, de différence et de hiérarchie. chacune propose une analyse féministe innovante qui est en quelque sorte motivée dans et par le défi poststructuraliste. 'Feminists Theorize The Political' aborde une série de préoccupations féministes, y compris la liberté productive, la loi anti-discrimination, le viol et la formulation du pouvoir en termes d'exclusion, de différence et de hiérarchie.
Keywords: 1900-1999; 1990-1999; anthologie; approches et analyses; cours; cycles supérieurs; discipline; fem9000; philosophie; philosophie politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; sciences humaines; sex3383

Social Criticism without Philosophy: An Encounter between Feminism and Postmodernism - Fraser, Nancy; Nicholson, Linda J. (Feminism/postmodernism, 1990)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; états-unis

Gender and knowledge: Elements of a postmodern feminism - Hekman, Susan J. (Northeastern University Press, 1990)
The aim of the book is to explore the connection between two perspectives that have had a profound effect upon contemporary thought: post-modernism and feminism. Through bringing together and systematically analysing the relations between these, Hekman is able to make a major intervention into current debates in social theory and philosophy. The critique of Enlightenment knowledge, she argues, is at the core of both post-modernism and feminism. Each also offers a basis for critical reflections about the other. In particular, post-modern philosophy provides a means of criticizing aspects of contemporary feminism and thus contributing to the development of a more sophisticated approach to current feminist issues.
Keywords: 1700-1799; 1900-1999; 1980-1989; approches et analyses; cours; discipline; europe; fem1000; france; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; études culturelles

Feminism/postmodernism - Nicholson, Linda J. (Thinking gender, 1990)
In this anthology, prominent contemporary theorists assess the benefits and dangers of postmodernism for feminist theory. The contributors examine the meaning of postmodernism both as a methodological position and a diagnosis of the times. They consider such issues as the nature of personal and social identity today, the political implications of recent aesthetic trends, and the consequences of changing work and family relations on women's lives. Contributors: Seyla Benhabib, Susan Bordo, Judith Butler, Christine Di Stefano, Jane Flax, Nancy Fraser, Donna Haraway, Sandra Harding, Nancy Hartsock, Andreas Huyssen, Linda J. Nicholson, Elspeth Probyn, Anna Yeatman, Iris Young.
Keywords: 1900-1999; 1980-1989; amériques; anthologie; approches et analyses; cours; discipline; fem1000; philosophie; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; théories culturelles; théories féministes; états-unis

Histoire de la sexualité I. La volonté de savoir - Foucault, Michel (Bibliothèque des histoires, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; his4860; histoire; histoire de la sexualité; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques

L’hypothèse répressive - Foucault, Michel (Histoire de la sexualité. 1. La volonté de savoir, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; histoire; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques